Comparison of methods for calculating internal work of elite running. - Purkiss, Sheila B. A. (University of Ottawa (Canada), 1996)
There are two basic models that are used to calculate the internal work involved in movement. The first, an energy-based model, calculates the changes in the energy of the segments. There are many variations of this model but Aleshinsky (1986) has shown that this approach lacks mathematical validity. The other, a power-based model, integrates the joint powers to find work. A modified power model (using absolute values) was shown by Aleshinsky (1986) to be mathematically valid but has only been used in two studies (Chapman et al., 1987; Caldwell and Forrester, 1992) each having only one subject. A version of this model was used in this study and was termed the absolute power method. For comparison purposes a modified version of the energy approach, called the absolute work method, was used. The internal work was then normalized for body mass and running velocity to obtain the "internal biomechanical cost" (IBC). The IBCs of normal running for four elite male and four elite female runners were compared to their IBCs of four inefficient running styles. The absolute power method was able to detect that the inefficient runs produced significantly higher internal work than normal running in 30 out of 32 cases (94%). Absolute work (the energy approach) could detect the inefficient runs in only 15 out of 32 cases (46%). As well, the absolute work approach was shown to be more variable and less reliable than the absolute power approach. The absolute power method also proved to be a useful tool for examining the work performed at each joint during a movement, thereby providing insight into where significant inefficiencies occur.
Keywords: Health Sciences, Recreation.